2007
DOI: 10.2174/092986707781389628
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Asthma: Can They Give Us Mechanistic Insights into the Role of Nitric oxide?

Abstract: New clinical practice guidelines for patients with asthma include the recommendation to monitor exhaled breath nitric oxide (NO) levels. NO concentrations in exhaled breath are increased in asthmatics and increased NO levels correlate with worsening airway inflammation and asthma symptoms. The multiple roles of NO in the lung have not been delineated clearly. Clinical trials are being performed presently that test the apparently conflicting hypotheses that either donors or inhibitors of NO in the lung are effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
1
21
0
1
Order By: Relevance
“…iNOS-associated protein nitration and tissue damage are partially responsible for allergen-induced eosinophilia following exposure Although the role of iNOS in the pathogenesis of allergeninduced airway inflammation has yet to be fully elucidated [25], it is widely accepted that the potential mechanism by which iNOS contributes to disease pathogenesis is through the mediation of tissue damage as a result of the excessive production of NO and its by-product ONOO -. Accordingly, the present study began by addressing the association between iNOS-mediated tissue damage and airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…iNOS-associated protein nitration and tissue damage are partially responsible for allergen-induced eosinophilia following exposure Although the role of iNOS in the pathogenesis of allergeninduced airway inflammation has yet to be fully elucidated [25], it is widely accepted that the potential mechanism by which iNOS contributes to disease pathogenesis is through the mediation of tissue damage as a result of the excessive production of NO and its by-product ONOO -. Accordingly, the present study began by addressing the association between iNOS-mediated tissue damage and airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, however, the level of exhaled NO has been reliably associated with severity of disease symptoms in asthmatics [3]. A few reports show a direct role for iNOS in the process of eosinophil recruitment in that inhibition of iNOS, either pharmacologically or by a gene knockout, reduces airway infiltration by inflammatory cells, especially eosinophils, in models of allergen-induced lung inflammation (reviewed in [25]). Furthermore, two very recent reports showed that polymorphisms in the iNOS gene may be important for asthma protection or susceptibility [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 and Figure 1A). Although iNOS expression and F E NO are increased in asthma and promote inflammatory injury via nitration (2,4), airway hyper -responsiveness is not diminished in mice with genetic deletion of iNOS (5), and arginine-analog inhibitors of iNOS pathways have poor efficacy in asthma (6). This caused us to consider that metabolism of arginine may mechanistically contribute to asthma through pathways other than generation of NO.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, allergen-induced airway inflammation and AHR were more pronounced in NOS2 knock-out mice than in wild type animals [74], although unchanged AHR [75] and inflammation [75,76] as well as reduced inflammation [77,78] have also been reported (for a comprehensive review on the role of NOS isoforms in asthma, see Mathrani et al [79]). …”
Section: Role Of Altered No Metabolism In Acute Allergeninduced Ahrmentioning
confidence: 99%